AWS Essentials and Solutions Architect Associate the Total Course - Seminars, Total; Carpenter, Tom (Packt Publishing, 2019)
New for 2019! Start with the basics, then learn everything you need to know to pass the AWS Solutions Architect exam About This Video Learn the basics of AWS and set up a free AWS account to run an instance Grasp AWS essentials and prepare for the AWS Solutions Architect - Associate certification In Detail Are you looking to learn more about AWS and what it can do for you or your company? Have you heard about it, but don't know how to take your business and network solutions to the AWS cloud? Perhaps you're a seasoned network techie looking to become an AWS Certified Solutions Architect Associate. If you can relate to any of those, the AWS Essentials and Solutions Architect Associate course is for you. This course includes both AWS Technical Essentials and AWS Certified Solutions Architect - Associate courses. If you're new to AWS and looking for a crash course to get to grips with the foundations, we recommend that you start right from the beginning with the Technical Essentials course, which isn't a certification exam prep course and doesn't cover exam domains, however, the following is a list of what it covers: Terminology and concepts related to the AWS platform How to navigate the AWS Management Console Key concepts for AWS security measures and AWS Identity and Access Management (IAM) Foundational services-Amazon Elastic Compute Cloud (Amazon EC2), Amazon Virtual Private Cloud (Amazon VPC), Amazon Simple Storage Service (Amazon S3), and Amazon Elastic Block Store (Amazon EBS) Database services-Amazon DynamoDB and Amazon Relational Database Service (Amazon RDS) Management services-AWS Auto Scaling, Amazon CloudWatch, Elastic Load Balancing (ELB), and AWS Trusted Advisor Once you're well-versed with the basics, you'll move on to the AWS Solutions Architect - Associate video course, which will take you through the exam domains which are as follows: Domain 1: Design Resilient Architectures (34%) Domain 2: Define Performant Architectures (24%) Domain 3: Specify Secure Applications and Architectures (26%) Domain 4: Design Cost-Optimized Architectures (10%) Domain 5: Define Operationally Excellent Architectures (6%) Downloading the example code for this course: You can download the example code files for this course on GitHub at the following link: https://github.com/PacktPublishing/AWS-Essentials-and-Solutions-Architect-Associate-The-Total-Course . If you require support please email: customercarepackt.com.
Online resource; Title from title screen (viewed July 5, 2019)
Keywords: Amazon Web Services (Firm) -- Study guides -- Examinations; Cloud computing -- Study guides -- Examinations; Web services -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Computer technicians -- Certification; Infonuagique; Examens; Guides de l'étudiant; Services Web; Examens; Guides de l'étudiant; Electronic videos